2022
DOI: 10.3389/fimmu.2022.967304
|View full text |Cite
|
Sign up to set email alerts
|

Composition and regulation of the immune microenvironment of salivary gland in Sjögren’s syndrome

Abstract: Primary Sjögren’s syndrome (pSS) is a systemic autoimmune disease characterized by exocrine gland dysfunction and inflammation. Patients often have dry mouth and dry eye symptoms, which seriously affect their lives. Improving dry mouth and eye symptoms has become a common demand from patients. For this reason, researchers have conducted many studies on external secretory glands. In this paper, we summarize recent studies on the salivary glands of pSS patients from the perspective of the immune microenvironment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 203 publications
(217 reference statements)
0
4
0
Order By: Relevance
“…Characterised by chronic inflammation, ageing and hypoxia, the immune microenvironment of salivary glands in pSS was dominated by CD4 + T cells, with the abundance of CD8 + T cells, B cells and plasma cells being relatively low. Complex interactions between infiltrating immune cells and tissue-resident cells facilitate disease progression in a location-and time-dependent manner (61,62). Human monocytes constitute approximately 10% of peripheral blood leukocytes (63).…”
Section: Discussionmentioning
confidence: 99%
“…Characterised by chronic inflammation, ageing and hypoxia, the immune microenvironment of salivary glands in pSS was dominated by CD4 + T cells, with the abundance of CD8 + T cells, B cells and plasma cells being relatively low. Complex interactions between infiltrating immune cells and tissue-resident cells facilitate disease progression in a location-and time-dependent manner (61,62). Human monocytes constitute approximately 10% of peripheral blood leukocytes (63).…”
Section: Discussionmentioning
confidence: 99%
“…Aberrant DNA methylation has also been implicated in non-immune cells. Considering that SGECs play an essential function in the emergence of SjS ( 140 ), it has been found that SGECs also play a significant function in the immune regulation in the pathophysiology of SjS and influencing the initiation and continuation of autoimmune response and inflammation ( 7 , 141 , 142 ). As SjS advances, the fundamental variations in the proteome of SGECs between SjS and healthy controls provide tangible evidence of SGEC transformation into an innate immune cell ( 143 ).…”
Section: Association Of Salivary Gland Epithelial Cells With Dna Meth...mentioning
confidence: 99%
“…Sjögren's syndrome (SS) is a chronic inflammatory autoimmune disease characterized by diminished secretory function of the exocrine glands (1)(2)(3)(4)(5)(6)(7)(8)(9). It affects approximately 1% of the general population and up to 3% of people above the age of fifty, with women accounting for more than 90% of diagnosed cases (10,11).…”
Section: Introductionmentioning
confidence: 99%